2020
DOI: 10.1002/jez.2427
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for invasion: Assessing risk of infection by chytrid fungi in southeastern plethodontid salamanders

Abstract: Understanding the responses of naïve communities to the invasion of multihost pathogens requires accurate estimates of susceptibility across taxa. In the Americas, the likely emergence of a second amphibian pathogenic fungus (Batrachochytrium salamandrivorans, Bsal) calls for new ways of prioritizing disease mitigation among species due to the high diversity of naïve hosts with priorB. dendrobatidis(Bd) infections. Here, we applied the concept of pathogenic potential to quantify the virulence of chytrid fungi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 71 publications
(112 reference statements)
0
19
0
Order By: Relevance
“…Infected amphibian skin and in culture transcriptome data. We selected RNA-Seq data from Bd in culture studies (21,22,31,33) and amphibian infection trials (21,22,(28)(29)(30)32,(34)(35)(36)(37) and generated new infection transcriptome data for two amphibian species (see Table S1 for NCBI Short Read Archive accession codes and further information about transcriptome files). Data selection was made based on sequencing strategy (Illumina sequencing technology), experiment day, sequencing coverage, and number of biological replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infected amphibian skin and in culture transcriptome data. We selected RNA-Seq data from Bd in culture studies (21,22,31,33) and amphibian infection trials (21,22,(28)(29)(30)32,(34)(35)(36)(37) and generated new infection transcriptome data for two amphibian species (see Table S1 for NCBI Short Read Archive accession codes and further information about transcriptome files). Data selection was made based on sequencing strategy (Illumina sequencing technology), experiment day, sequencing coverage, and number of biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Data selection was made based on sequencing strategy (Illumina sequencing technology), experiment day, sequencing coverage, and number of biological replicates. Likewise, new transcriptomes from eleven skin samples of experimentally infected Eleutherodactylus coqui (36) and Desmognathus auriculatus (37) individuals were sequenced on an Illumina NovaSeq 6000 S4 2x150 flow cell after RNA extraction and cDNA library preparation using, respectively, QIAGEN RNeasy® Plus Mini Kit and NEBNext® Ultra™ II Directional RNA Library Prep Kit following manufacturers' protocols. We measured the quantity and quality of the RNA and cDNA libraries using Qubit and Bioanalyzer.…”
Section: Methodsmentioning
confidence: 99%
“…In the SI, Friday et al (2020) showed B. salamandrivorans infection in five salamanders species. The authors demonstrated an interspecific variation in the salamanders' survival when exposed to the fungus, from complete survival for Desmognatus apalachicolae, D. conanti , and Eurycea guttolineata , to almost 100% mortality for D. auriculatus and E. cirrigera .…”
Section: Emerging Fungal Pathogensmentioning
confidence: 99%
“…The authors demonstrated an interspecific variation in the salamanders' survival when exposed to the fungus, from complete survival for Desmognatus apalachicolae, D. conanti , and Eurycea guttolineata , to almost 100% mortality for D. auriculatus and E. cirrigera . Higher mortality was also associated with higher B. salamandrivorans infection intensities in the susceptible species (Friday et al, 2020). Moreover, a co‐infection of Batrachochytrium salamandrivorans and B. dendrobatidis in D. auriculatus was associated with higher mortality, demonstrating that for some salamander species, either or both of these pathogens could drive the species to extinction (Friday et al, 2020).…”
Section: Emerging Fungal Pathogensmentioning
confidence: 99%
See 1 more Smart Citation